Strain in teaching and research: structural equation modeling approach - Idris, Mohd Kamel (Faculty of Economics and Management, Universiti Putra Malaysia, 2010)
A transactional model of stress is expanded to incorporate role stressors (i.e. role overload, role ambiguity and role conflict) as the antecedents of strain and the outcomes of strain including cynicism, professional efficacy, and organizational commitment. This integrated model clarifies the impact of role stressors on strain and the impact of strain on cynicism, professional efficacy and organizational commitment on a study among academics in Malaysian public universities. The perceived organizational support, peer support, and self-efficacy are added in consideration of research indicating that those variables can buffer the effect of role stressors on strain. A longitudinal survey with a six month time interval yielded 357 respondents for Time1 and 210 respondents for Time 2. A structural equation modeling (SEM) approach was used to test this model using data at Time 1 with a cross-validation on the sample at Time 2. The result of the study indicated that role ambiguity account for the strongest direct effect on strain; strain had the strongest direct effect on cynicism. The path analysis revealed that the paths of role ambiguity, strain, cynicism, organizational commitment and turnover intention was a critical path of the model.